Pengaruh Struktur Modal, Kebijakan Dividen Dan Keputusan Investasi Terhadap Nilai Perusahaan - Gayatri, Ni Luh Putu Rassri; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 3 No 6 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE The firm value reflects the present value of expected future earnings. Financial management functions to maximize the value of the company. The purpose of this study was to determine the significance of the effect of capital structure (DER), dividend policy (DPR) and investment decisions (PER) on firm value (PBV) at a manufacturing company in BEI 2008-2012 period. The number of companies listed on the Stock Exchange was 146 company, using purposive sampling method in the determination of the sample obtained by 9 companies in the sample. The data analysis technique used is multiple linear regression with SPSS 15 for windows. The results of that study capital structure and investment decisions significant positive effect on firm value, while the dividend policy has no significant effect on firm value. Keywords : capital structure , dividend policy , investment decisions , firm value